FTO regulates ocular angiogenesis via m6A-YTHDF2-dependent mechanism. (August 2020) - Shan, Kun; Zhou, Rong-mei; Xiang, Jun; Sun, Ya-nan; Liu, Chang; Lv, Meng-wei; Xu, Jian-jiang
Abstract: Pathological ocular angiogenesis commonly results in visual impairment or even blindness. Unveiling the mechanisms of pathological angiogenesis is critical to identify the regulators and develop effective targeted therapies. Here, we used corneal neovascularization (CNV) model to investigate the mechanism of pathological ocular angiogenesis. We show that N 6 -methyladenosine (m 6 A) mRNA demethylation mediated by fat mass- and obesity-associated protein (FTO) could regulate endothelial cell (EC) function and pathological angiogenesis during CNV. FTO levels are increased in neovascularized corneas and ECs under pathological conditions. In vitro silencing of FTO in ECs results in reduced cellular proliferation, migration, and tube formation under both basal and pathological conditions. Furthermore, FTO silencing attenuates suture-induced CNV in vivo. Mechanically, FTO silencing in ECs could increase m 6 A methylation levels in critical pro-angiogenic genes, such as FAK, leading to decreased RNA stability and increased RNA decay through m 6 A reader YTHDF2. Our study demonstrates that FTO regulates pathological ocular angiogenesis by controlling EC function in an m 6 A-YTHDF2-dependent manner. Highlights: We used cornea as a unique system for studying the mechanism of pathological ocular angiogenesis. FTO regulates the progression of corneal neovascularization. FTO regulates vascular endothelial function via m 6 A-YTHDF2 mechanism. Targeting m 6 A modification is a potential therapy for pathological ocular angiogenesis.